2007
DOI: 10.1124/jpet.107.125336
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Cannabinoid Anandamide Inhibits Cromakalim-Activated K+Currents in Follicle-EnclosedXenopusOocytes

Abstract: The effect of the endogenous cannabinoid anandamide on K ϩ currents activated by the ATP-sensitive potassium (K ATP ) channel opener cromakalim was investigated in follicle-enclosed Xenopus oocytes using the two-electrode voltage-clamp technique. Anandamide (1-90 M) reversibly inhibited cromakaliminduced K ϩ currents, with an IC 50 value of 8.1 Ϯ 2 M. Inhibition was noncompetitive and independent of membrane potential. Coapplication of anandamide with the cannabinoid type 1 (, or pertussis toxin (5 g/ml) did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Unlike THC, it is virtually inactive at both CB1 and CB2 receptors (Pertwee, 2009; for review, see Izzo et al, 2009). CB1 and CB2 receptors are not expressed in X. laevis oocytes (Hejazi et al, 2006;Oz et al, 2007). Therefore, it is unlikely that the effect of CBD on 5-HT 3 receptors is mediated by the activation of CB1 or CB2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike THC, it is virtually inactive at both CB1 and CB2 receptors (Pertwee, 2009; for review, see Izzo et al, 2009). CB1 and CB2 receptors are not expressed in X. laevis oocytes (Hejazi et al, 2006;Oz et al, 2007). Therefore, it is unlikely that the effect of CBD on 5-HT 3 receptors is mediated by the activation of CB1 or CB2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, WIN55212, the selective agonist of CB1 receptors, markedly decreased activity on voltage-gated Na channels in dorsal root (13) and trigeminal ganglion neurons of rats (8) and frog parathyroid cells (20). Moreover, in experiments performed in follicular cells of Xenopus oocytes anandamide blocks cromakalim-dependent K currents, altering the responses to gonadotropin or progesterone (23). Because anandamide has been found to be synthesized in the renal medulla (6), it is likely that anandamide could be an autacoid or paracrine factor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that anandamide potently inhibits amino-acid transporters in a Na-dependent manner in neural tissue (26). Also, in parathyroid and neuronal tissues anandamide blocks the Na (20) and K currents, controlling hormonal-derived responses (23).…”
mentioning
confidence: 99%
“…Potassium Channels 3.5.1 ATP-Sensitive Inward Rectifier K ATP Channels of the 2TM Domain Family Oz et al (2007) have obtained evidence from experiments with Xenopus oocytes that anandamide can act independently of CB 1 or CB 2 cannabinoid receptors as a non-competitive inhibitor of K ATP channels (IC 50 ¼ 8.1 μM) and that this endocannabinoid also inhibits […”
Section: 5mentioning
confidence: 99%